THE ROLE OF SCHOOL TV IN INCREASING PARENTAL PARTICIPATION TO SUPPORT THE LEARNING PROCESS IN PAUD - Diana Indah Palupi; Emma Rahmani; Erlin Yusnita; Dian Farista; Sri Watini (Sean Institute, 2022)
One of the media in this digitalization era that is considered very suitable for the development of early childhood communication skills is school TV by utilizing the